Corn protein hydrolysate as a new structural modifier for soybean protein isolate based O/W emulsions. (January 2020) - Wang, Yong-Hui; Wang, Jin-Mei; Wan, Zhi-Li; Yang, Xiao-Quan; Chen, Xiao-Wei
Abstract: In the work, a new approach to modify the structure of soybean protein isolate (SPI) stabilized oil in water (O/W) emulsions based on peptides induced protein aggregation was reported. The results indicated that corn protein hydrolysate (CPH) considerably changed the physical characteristics of the SPI stabilized emulsions under the heating conditions, and the emulsions changed from flow state to semi-solid one with the increasing of CPH in CPH/SPI mixture. The results from microstructure investigation showed that more SPI molecules were adsorbed at the O/W interface and the interfacial thickness could increase due to the presence of CPH. Moreover, the study on rheological behavior showed that the apparent viscosity, viscoelasticity and thixotropic properties of the emulsions all could be modified by controlling CPH content. The structural changes of SPI-based emulsions may be attributed to the hydrophobic interactions of CPH and SPI under heating treatment, and CPH may have enhanced SPI molecular connection (at the interface or aqueous phase) through the unfolded hydrophobic locus. These findings suggested that protein hydrolysate could be used as a new structural modifier for native protein stabilized emulsions. Highlights: CPH caused heating aggregation of SPI at O/W interface and in bulk solution. CPH induced flocculation of the SPI stabilized emulsions under heating condition. CPH addition hugely increased surficial protein coverage of the emulsions. CPH can be used as a new structural modifier for O/W emulsions.